Posttraumatic Stress Disorder Symptoms and Reckless Behaviors: A Network Analysis Approach. Issue 1 (22nd February 2020) - Armour, Cherie; Greene, Talya; Contractor, Ateka A.; Weiss, Nicole; Dixon‐Gordon, Katherine; Ross, Jana
Abstract: Existing literature indicates a theoretical and empirical relation between engagement in reckless behaviors and posttraumatic stress disorder (PTSD). Thus, the DSM‐5 revision of the PTSD nosology added a new "reckless or self‐destructive behavior" (RSDB) symptom (Criterion E2). The current study applied a network analytic approach to examine the item‐level relations among a range of reckless behaviors and PTSD symptom clusters. Participants were recruited from Amazon's Mechanical Turk ( N = 417), and network analysis was conducted with 20 variables: six PTSD symptom clusters, corresponding to the hybrid model of PTSD (Armour et al., 2015) and excluding the externalizing behavior cluster (Community 1), and 14 items related to reckless behavior (Community 2). The results showed that the network associations were strongest within each construct (i.e., within PTSD and within reckless behaviors), although several bridge connections (i.e., between PTSD clusters and reckless behaviors) were identified. Most reckless behavior items had direct associations with one or more PTSD symptom clusters. The present findings support the existence of close relations between a variety of reckless behaviors and PTSD symptom clusters beyond their relations with DSM Criterion E2. The results provide testable hypotheses about the associations between specific reckless behaviors and PTSD symptom clusters, which may inform future research. Resumen: Spanish Abstracts by Asociación Chilena de Estrés Traumático (ACET) Síntomas del trastorno de estrés postraumático y comportamientos imprudentes: un enfoque de análisis de red TEPT Y COMPORTAMIENTO IMPRUDENTE La literatura existente indica una relación teórica y empírica entre la participación en comportamientos imprudentes y el trastorno de estrés postraumático (TEPT). Por lo tanto, la revisión DSM‐5 de la nosología del TEPT agregó un nuevo síntoma de comportamiento imprudente o autodestructivo (RSDB en su sigla en inglés) (Criterio E2). El estudio actual aplicó un enfoque analítico de red para examinar las relaciones a nivel de ítem entre una gama de comportamientos imprudentes y grupos de síntomas de TEPT. Los participantes fueron reclutados de Amazon Mechanical Turk ( N = 417) y el análisis de red se realizó con 20 variables: seis grupos de síntomas de TEPT (comunidad 1) correspondientes al modelo híbrido de TEPT (Armor et al., 2015), excluyendo el grupo de Comportamiento de externalización; y 14 elementos de comportamiento imprudente (comunidad 2). Los resultados mostraron que las asociaciones de red eran más fuertes dentro de cada construcción (es decir, dentro del TEPT y dentro de los comportamientos imprudentes), aunque se identificaron varias conexiones puente (es decir, entre grupos de TEPT y comportamientos imprudentes). La mayoría de los elementos de comportamiento imprudente tenían relaciones directas con uno o más grupos de síntomas de TEPT. Los hallazgos respaldan la existencia de relaciones cercanas entre una variedad de comportamientos imprudentes y grupos de síntomas de TEPT más allá de su relación con el Criterio E2. Los resultados proporcionan hipótesis comprobables sobre las relaciones entre comportamientos imprudentes específicos y grupos de síntomas de TEPT que pueden informar futuras investigaciones. 抽象: Traditional and Simplified Chinese Abstracts by the Asian Society for Traumatic Stress Studies (AsianSTSS) 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯 Posttraumatic Stress Disorder Symptoms and Reckless Behaviors: A Network Analysis Approach Traditional Chinese 標題: 創傷後壓力症症狀與魯莽行為:網絡分析法 撮要: 目前已有的研究反映, 魯莽行為跟創傷後壓力症(PTSD)之間存在理論及實證關係。因此, DSM‐5對PTSD的疾病分類作出修正, 新增魯莽或自我傷害行為(RSDB)這個症狀 (準則E2) 。本研究採用網絡分析法, 檢視一系列的魯莽行為跟PTSD症狀聚類在項目層面的關係。我們透過亞馬遜土耳其機器人(Amazon Mechanical Turk) 採集樣本(N = 417), 然後以20個變量進行網絡分析:PTSD混合模型(Armour et al., 2015)中的六個PTSD症狀聚類 (社群一), 當中剔除外化行為聚類和14個魯莽行為項目 (社群二) 。結果反映, 雖然我們發現了幾個橋接 (即在PTSD症狀聚類與魯莽行為之間), 但各個構念內裡的網絡關連最強 (即在PTSD內裡及魯莽行為內裡) 。大多數魯莽行為項目跟一個或以上的PTSD聚類有直接關連。結果證明, 在PTSD症狀聚類跟準則E2的關係以外, 各種不同的魯莽行為跟PTSD症狀聚類都有密切關係。是次發現為特殊的魯莽行為和PTSD症狀聚類的關係提供了可供測試的假設, 可能有助未來研究。 Simplified Chinese 标题: 创伤后压力症症状与鲁莽行为:网络分析法 撮要: 目前已有的研究反映, 鲁莽行为跟创伤后压力症(PTSD)之间存在理论及实证关系。因此, DSM‐5对PTSD的疾病分类作出修正, 新增鲁莽或自我伤害行为(RSDB)这个症状 (准则E2) 。本研究采用网络分析法, 检视一系列的鲁莽行为跟PTSD症状聚类在项目层面的关系。我们透过亚马逊土耳其机器人(Amazon Mechanical Turk) 采集样本(N = 417), 然后以20个变量进行网络分析:PTSD混合模型(Armour et al., 2015)中的六个PTSD症状聚类 (社群一), 当中剔除外化行为聚类和14个鲁莽行为项目 (社群二) 。结果反映, 虽然我们发现了几个桥接 (即在PTSD症状聚类与鲁莽行为之间), 但各个构念内里的网络关连最强 (即在PTSD内里及鲁莽行为内里) 。大多数鲁莽行为项目跟一个或以上的PTSD聚类有直接关连。结果证明, 在PTSD症状聚类跟准则E2的关系以外, 各种不同的鲁莽行为跟PTSD症状聚类都有密切关系。是次发现为特殊的鲁莽行为和PTSD症状聚类的关系提供了可供测试的假设, 可能有助未来研究。